Systematic Analysis of Lysine Lactylation in the Plant Fungal Pathogen Botrytis cinerea - Gao, Mingming; Zhang, Ning; Liang, Wenxing (Frontiers in Microbiology, 2020)
Lysine lactylation (Klac) is a newly discovered histone post-translational modification (PTM), playing important roles in regulating transcription in macrophages. However, the extent of this PTM in non-histone proteins remains unknown. Here, we report the first proteomic survey of this modification in Botrytis cinerea, a destructive necrotrophic fungal pathogen distributed worldwide. After a global lysine lactylome analysis using LC-MS/MS, we identified 273 Klac sites in 166 proteins, of which contained in 4 types of modification motifs. Our results show that the majority of lactylated proteins were distributed in nucleus (36%), mitochondria (27%) and cytoplasm (25%). The identified proteins were found to be involved in diverse cellular processes. Most strikingly, Klac was found in 43 structural constituent proteins of ribosome, indicating an impact of Klac in protein synthesis. Moreover, 12 lactylated proteins participated in fungal pathogenicity, suggesting a potential role for Klac in this process. Protein interaction network analysis suggested that a mass of protein interactions are regulated by lactylation. The combined data sets represent the ﬁrst report of the lactylome of B. cinerea and provide a good foundation for further explorations of Klac in plant fungal pathogens.